Food systems profile for Amhara Region, Ethiopia - Ethiopian Public Health Institute (EPHI); Food and Nutrition Society of Ethiopia (FoNSE); Bioversity International and the International Center for Tropical Agriculture (2026)
Food systems encompass the entire range of actors and their interlinked value-adding activities involved in the production, aggregation, processing, distribution, consumption, and disposal of food products. Food systems influence diets by determining what kinds of foods are produced, which foods are accessible both physically and economically, and peoples’ food preferences. Sustainable food systems are critical for ensuring food and nutrition security, people’s livelihoods, and environmental sustainability. Transforming food systems and making them more sustainable, equitable, and inclusive will only be possible through collaboration and participation from governmental and non-governmental organizations, including private sector actors. Accordingly, the concept of developing a food system profile evolved to support this transformation by creating a common platform that facilitates the implementation of appropriate interventions across all stakeholders. The development of the Amhara Region Food System Profile was achieved through a consultative process, which brought together many relevant stakeholders operating in the region. Consultative workshops were carried out during which appropriate indicators based on the food system components across all sectors were selected and prioritized. The food system profile of the region with respect to the selected indicators was visualized and briefly described based on the data collected in recent years. In addition to providing guidance for decision making, sectoral planning, and identification of potential intervention areas in the Amhara region, the food system profile will also be used as a reference document for other regions/partners that plan to develop their own regional food system profiles. During the development of the food system profile, several valuable lessons were gained. The main lessons included approaches for engaging stakeholders to discuss their status with respect to food system indicators, identifying the most regionally relevant indicators and supporting them with appropriate data, and assessing how different sectors across the regional food systems are performing. Another important lesson included recognizing gaps, challenges, and trade-offs in the identification and application of pertinent indicators, which can be regarded as opportunities for strengthening implementation, monitoring, and evaluation. Among the many challenges encountered were late or non-responses from some stakeholders regarding workable indicators, lack of data or documentation, and lack of trend data (i.e., inconsistent data/records) across years/months. Based on lessons taken from the food system profile development process, the following key areas of interventions are proposed: assigning a monitoring and evaluation unit with appropriate experts; identification, selection, and prioritization of indicators across all relevant sectors; systematic recording and documentation of performance data with respect to prioritized indicators; creating a common regional platform (i.e., central database); and alignment of sectoral planning and budgeting with the prioritized indicators.